LIFE IS A PLAY: reading David Mamet's sexual perversity in Chicago and Glengarry Glen Ross through Cognitive Poetics - Ghaeli, Rosa; Pirnajmuddin, Hossein (Penerbit Universiti Kebangsaan Malaysia, 2016)
One of the concerns of Cognitive Poetic critics has been with the issue of how literary authors make meaning by means of metaphor. Building on the Cognitive Linguistic theories of metaphor, the field of Cognitive Poetics has been concerned, among its many diverse areas, with the studying of metaphor in literary texts. Proposing the Conceptual Metaphor Theory (CMT), cognitive linguists George Lakoff and Mark Johnson argued in Metaphors We Live By that our conceptual system is metaphorically shaped. In addition, they claimed that the metaphoric linguistic expressions are the manifestation of the fundamental conceptual metaphors forming individuals' cognitions. Conceptual metaphors were defined as the underlying structures of these expressions by means of which people comprehend intangible concepts through more tangible ones. Using the Conceptual Metaphor Theory (CMT), the present essay explores the conceptual metaphor of LIFE IS A PLAY in David Mamet's Sexual Perversity in Chicago and Glengarry Glen Ross. In these plays, Mamet depicts a world in which performance, in its theatrical sense, becomes the characters' survival strategy and a manner of living. As one of the most influential playwrights of his time, Mamet has always been concerned with the issues which most afflict America. He finds the ills of his society manifested in the relation among people. An attempt is made to explain the ways in which life-as-play finds expression both linguistically and thematically in the different contexts of these works.